2006
DOI: 10.1016/j.ccr.2005.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Cbfβ-SMMHC induces distinct abnormal myeloid progenitors able to develop acute myeloid leukemia

Abstract: The acute myeloid leukemia (AML)-associated CBF beta-SMMHC fusion protein impairs hematopoietic differentiation and predisposes to leukemic transformation. The mechanism of leukemia progression, however, is poorly understood. In this study, we report a conditional Cbfb-MYH11 knockin mouse model that develops AML with a median latency of 5 months. Cbf beta-SMMHC expression reduced the multilineage repopulation capacity of hematopoietic stem cells (HSCs) while maintaining their numbers under competitive conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
192
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(210 citation statements)
references
References 49 publications
18
192
0
Order By: Relevance
“…This difference is most likely caused by the increased size of the Cbfb-SMMHC þ preleukemic progenitor pool in the BM of the conditional knock-in mice. 44 Thus, the increased proliferative capacity of MN1 overexpressing cells may enlarge the pool of inv(16) cells enough to promote additional mutations allowing the leukemia to emerge. We favor this possibility because Southern blotting suggested that mouse inv(16)/MN1 leukemia is oligoclonal rather than polyclonal, although our analysis cannot exclude that the oligoclonality derives from the concomitant MN1-induced MPD in these transplanted mice.…”
mentioning
confidence: 99%
“…This difference is most likely caused by the increased size of the Cbfb-SMMHC þ preleukemic progenitor pool in the BM of the conditional knock-in mice. 44 Thus, the increased proliferative capacity of MN1 overexpressing cells may enlarge the pool of inv(16) cells enough to promote additional mutations allowing the leukemia to emerge. We favor this possibility because Southern blotting suggested that mouse inv(16)/MN1 leukemia is oligoclonal rather than polyclonal, although our analysis cannot exclude that the oligoclonality derives from the concomitant MN1-induced MPD in these transplanted mice.…”
mentioning
confidence: 99%
“…The transcription-factor fusions were the first recognized somatic mutations in AML genomes, 1,2 and all such fusions have been shown to be relevant for disease initiation in mice. [39][40][41][42] Our data show that some mutations that are common in AML (e.g., in DNMT3A, NPM1, CEPBA, IDH1/2, and RUNX1) are mutually exclusive of the transcription-factor fusions, suggesting that these mutations may have functions in the initiation of AML that are similar to the functions of fusion genes. We also identified a pattern of mutual exclusivity for mutations in genes within certain biologic classes, including those encoding the cohesins, proteins of the spliceosome, signaling proteins, and histone-modifying proteins, suggesting that one mutation in these pathways is generally adequate for AML pathogenesis.…”
Section: Discussionmentioning
confidence: 61%
“…Mature megakaryocytes express strikingly high levels of RUNX1 and low levels of RUNX3 (Levanon et al, 2001). Inducible inactivation in mice of either RUNX1 or CBFb causes rapid and profound disruption of megakaryocytic differentiation, with minimal impact on erythropoiesis (Ichikawa et al, 2004;Growney et al, 2005;Kuo et al, 2006;Putz et al, 2006). In addition, mice bearing hypomorphic CBFb alleles show defective megakaryopoiesis, confirming the lineage to be sensitive to the dosage of core binding factor (Talebian et al, 2007).…”
Section: Gata and Friend In Sickness And In Health: X-linked Thrombocmentioning
confidence: 90%